O audiovisual como ensino de libras através do Instagram - (:unkn) unknown (Universidade Federal do Pampa, 2024)
In this research, we sought to understand how audiovisual products from Sign Language Translators and Interpreters (TILS) profiles on Instagram work to teach Libras. There were 12 audiovisuals analyzed belonging to four different profiles, presented by TILS professionals and Libras teachers, with content more aimed at teaching Brazilian sign language to the listening public. To carry out the study, we have the following specific objectives: 1- Analyze the techniques used in the production of audiovisuais, from pre-production, production and post-production; 2- Check the aesthetic aspects that form visual communication with regard to the identity and visual pattern of the profile, the audiovisual language, the maintenance of the visual style in the use of colors and fonts used in editing the audiovisuais; 3- Analyze aspects of the presence of communication accessibility resources in the audiovisuais. The study has a qualitative, exploratory approach, with its theoretical foundation built within the following themes: Audiovisual; Teaching Libras; Instagram; Digital Education; Person with Disability; Accessible Audiovisual; Accessible Communication. It also uses, together, the methodological procedures of Content Analysis (Bardin, 2011), Moving Image Analysis (Rose, 2002) and Semi-structured Interview (Triviños, 1987) for data collection. In conclusion, evidence was found that, with regard to the use of audiovisuals as teaching, it is possible to understand that audiovisuals alone do not enable efficient learning of Libras, but that when consuming these contents actively on an Instagram profile , these audiovisuals become potential knowledge multipliers. Therefore, it can be said that the use of audiovisual to teach Libras, in a responsible way, can contribute to the expansion of knowledge of the language, a fact that can gradually have an impact on reducing communication barriers between deaf and hearing people.
Keywords: Língua de sinais - Ensino; Recursos audiovisuais; Instagram (Rede social on-line); Língua brasileira de sinais; Sign Language – Education; Audiovisual resources; CNPQ::CIENCIAS SOCIAIS APLICADAS